2023
DOI: 10.1177/00368504231206265
|View full text |Cite
|
Sign up to set email alerts
|

Overview of the impact of sleep monitoring on optimal performance, immune system function and injury risk reduction in athletes: A narrative review

Hadi Nobari,
Mojgan Banihashemi,
Saber Saedmocheshi
et al.

Abstract: Sleep is essential for a range of physiological and mental functions in professional athletes. There is proof that athletes may experience lower quality and quantity of sleep. While adequate sleep has been shown to have restorative effects on the immune system and endocrine system, facilitate nervous system recovery and the metabolic cost of wakefulness, and play a significant role in learning, memory, and synaptic plasticity, which can affect sports recovery, injury risk reduction, and performance. Sports per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 61 publications
(164 reference statements)
0
1
0
Order By: Relevance
“…In elite athletes, a case-controlled study reported that poor sleep was associated with a greater risk for upper respiratory tract and gastrointestinal symptoms [ 24 ]. Evidence has previously demonstrated a significant association between SHC and new injury risk in athletic populations; a study by Nobari and colleagues [ 34 ] involving 122 athletes discovered that <8 h of sleep per night increased the risk of injury by 65% [ 35 ]. While an explicit cause and effect cannot be determined from the nature of these findings, a clear reciprocal relationship between the variables is apparent.…”
Section: Discussionmentioning
confidence: 99%
“…In elite athletes, a case-controlled study reported that poor sleep was associated with a greater risk for upper respiratory tract and gastrointestinal symptoms [ 24 ]. Evidence has previously demonstrated a significant association between SHC and new injury risk in athletic populations; a study by Nobari and colleagues [ 34 ] involving 122 athletes discovered that <8 h of sleep per night increased the risk of injury by 65% [ 35 ]. While an explicit cause and effect cannot be determined from the nature of these findings, a clear reciprocal relationship between the variables is apparent.…”
Section: Discussionmentioning
confidence: 99%